DAYA PENGURANGAN HASIL TANGKAPAN SAMPINGAN (BYCATCH) DARI TIGA TIPE BYCATCH REDUCTION DEVICE (BRD) : PERCOBAAN TRAWL DI LAUT ARAFURA - Ronny I. Wahju; M. Fedi A. Sondita; Sugeng Hari Wisudo; John Haluan (Buletin PSP, 2008)
Study on the bycatch reducing capacity of three type of BRDs toward the bycatch was carried out in the Dolak waters in the Arafura Sea from 29 November until 9 Desember 2007. The objective of the research is to compare the reducing capacity of three types of BRD (TED super shooter, square mesh window, and fish eye) toward the bycath. The result of the research showed that from total 26 hauls 45 sppecies were identified comprises of 21 sppecies of fisher, 2 sppecies of shrimps and some sppecies of crabs. From those sppecies of fish 21 sppecies of economic fisher were utilized by the fishers. The result of wilcoxon sign test showed there is no statistically significant different in reducing the bycatch for three different types of BRDs. However, the fish eye reducing the bycatch up to 13.36% and the square mesh window 5.89%. In contrast, TED super shooter increasing the bycatch 4.66%. Those BRDs had influenced to the shrimp loss i.e 21.25% for the fish eye, 22.13% for the square mesh window, and 32.29% for the TED super shooter.